RETSAT Mutation Selected for Hypoxia Adaptation Inhibits Tumor Growth - Jiang, Xiulin; He, Yaomei; Shen, Qiushuo; Duan, Lincan; Yuan, Yixiao; Tang, Lin; Shi, Yulin; Liu, Baiyang; Zhai, Haoqing; Shi, Peng; Yang, Cuiping; Chen, Yongbin (Frontiers in Cell and Developmental Biology, 2021)
Hypoxia occurs not only in natural environments including high altitude, underground burrows and deep sea, but also in human pathological conditions, such as hypoxic solid tumors. It has been well documented that hypoxia related signaling pathway is associated with a poor clinical outcome. Our group has recently identified multiple novel genes critical for solid tumor growth comparing the genome-wide convergent/parallel sequence evolution of highland mammals. Among them, a single mutation on the retinol saturase gene (RETSAT) containing amino acid switch from glutamine (Q) to arginine (R) at the position 247 was identified. Here, we demonstrate that RETSAT is mostly downregulated in multiple types of human cancers, whose lower expression correlates with worse clinical outcome. We show that higher expression of RETSAT is positively associated with immune infiltration in different human cancers. Furthermore, we identify that the promoter region of RETSAT is highly methylated, which leads to its decreased expressions in tumor tissues comparing to normal tissues. Furthermore, we show that RETSAT knockdown promotes, while its overexpression inhibits, the cell proliferation ability of mouse embryonic fibroblasts (MEFs) and B16 in vitro. In addition, the mice carrying homozygous Q247R mutation (RETSATR/R) is more resistant to xenograft tumor formation, as well as DMBA/TPA induced cutaneous keratinocyte carcinoma formation, compared to littermate wild-type (RETSATQ/Q) mice. Mechanistic study uncovers that the oncogenic factor, the prolyl isomerase (PPIase) Pin1 and its related downstream signaling pathway, were both markedly repressed in the mutant mice compared to the wild-type mice. In summary, these results suggest that interdisciplinary study between evolution and tumor biology can facilitate identification of novel molecular events essential for hypoxic solid tumor growth in the future.